PREHISTORIC AND MODERN ART: INTEGRATION BETWEEN ANIMATION AND ANIMISM OF THE ARCHIPELAGO'S VISUAL HERITAGE - Afgana, Musa Pedro (International Journal of Social Service and Research, 2024)
This study aims to investigate the integration of prehistoric art elements into modern Indonesian art, particularly in animation and the works of Heri Dono. The qualitative approach facilitated an in-depth exploration of symbolic and animistic aspects of art and their reinterpretation in contemporary art practices. Data collection involved three main techniques: a comprehensive literature review, semi-structured interviews, and direct observation of relevant artworks. The findings of this study reveal a deep connection between prehistoric artworks and contemporary art, with a specific focus on HeriDono's works. The analysis highlights how prehistoric motifs and concepts from Sulawesi and Kalimantan cave paintings have been reinterpreted and adapted in the context of postmodernism and animation. These findings highlight the importance of prehistory art as a foundational element for contemporary art. This study provides a new insight into the continuity of cultural practices across time and their relevance in modern art, thereby enriching discussions on cultural relevance and artistic innovation in today's art landscape.